2016
DOI: 10.1186/s12872-016-0304-5
|View full text |Cite
|
Sign up to set email alerts
|

The values of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio in predicting 30 day mortality in patients with acute pulmonary embolism

Abstract: BackgroundvAcute pulmonary embolism (PE) is a life threatening disease. The treatment options depend on the severity of the disease and the mortality varies widely depending on the severity of the condition. It is important to identify patients who are at high risk of mortality. The aim of the present study was to explore the prognostic alues of neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) for 30-day mortality in patients with acute PE.MethodsThe study included 321 patients admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
4
35
0
Order By: Relevance
“…In our research, 101 patients were included, and 24 patients died within 30 days, corresponding to a 30day mortality rate of 23.8%. According to previous studies, the mortality rate of APE patients ranges from 8.1%-25.3% [12,[18][19][20]. Our results showed that the mortality of our cohort was within this range.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our research, 101 patients were included, and 24 patients died within 30 days, corresponding to a 30day mortality rate of 23.8%. According to previous studies, the mortality rate of APE patients ranges from 8.1%-25.3% [12,[18][19][20]. Our results showed that the mortality of our cohort was within this range.…”
Section: Discussionsupporting
confidence: 73%
“…The NLR is the comprehensive presentation of systemic in ammation and the balance between neutrophils and lymphocytes in CBCs. Previous studies have shown that an elevated NLR is associated with an increased rate of hospital mortality among patients with acute pulmonary embolism [13], acute exacerbation of chronic obstructive pulmonary disease [21], and acute type A aortic dissection [22]; of 30-day mortality among patients with acute pulmonary embolism [19], acute kidney injury [23], ST-elevation myocardial infarction [24], and intracerebral hemorrhage [25,26]; and of long-term mortality among patients with STelevation myocardial infarction [27], breast cancer [28] and epithelial ovarian cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…These markers were significantly elevated in nonsurvivors compared to survivors, which is consistent with prior reports. 15,16 Furthermore, we demonstrated that both NLR and PLR correlated with the PESI and sPESI scores. Platelet-to-lymphocyte ratio has been correlated with the sPESI score, but to our knowledge, an association between NLR and the PESI score or sPESI score has not been reported.…”
Section: Discussionmentioning
confidence: 80%
“…This finding differs from other studies, which have reported that neutrophil count can be markedly elevated in the setting of decreased lymphocytes in PE nonsurvivors. 15,16 The differences may reflect the highly variable state of the inflammatory milieu and the need for markers from multiple cell lines to acquire a global view of the immune response to PE. Both NLR and PLR are promising markers because they integrate cell counts that are routinely measured in clinical practice, offering timely information about inflammation status.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they reported a high negative predictive value (93.9%) rather than a positive one (36.5%). Ma et al [19] also suggested that NLR could predict 30-day mortality in patients with PTE. The results of our study confirm their results, while opening a new horizon for PTE evaluation.…”
Section: Discussionmentioning
confidence: 99%